CD155 promotes the progression of colorectal cancer by restraining CD8+ T cells via the PI3K/AKT/NF-κB pathway - Rongpu Liang; Liting Liu; Dongbing Ding; Yiquan Li; Jiannan Ren; Bo Wei (Cancer Immunology, Immunotherapy)
Abstract Background CD155 is a crucial factor in the regulation of T cell function and contributes to immune escape. CD155 upregulation has been found in several types of cancer. However, the mechanism by which CD155 regulates CD8+ T cell function in colorectal cancer remains unclear. Here we investigated the role and mechanism of CD155 in the regulation of CD8+ T cell function. Methods We studied the expression of CD155 in colorectal cancer tissues through western blot, immunohistochemistry, and the TCGA database. We verified the effects of CD155 on the functions of colorectal cancer cells and CD8+ T cells through in vitro experiments. We demonstrated that CD155 affects CD8+ T cell migration and thus promotes tumor growth in a mouse subcutaneous tumor model. We then tested the changes in the PI3K/AKT/NF-κB pathway in CD8+ T cells by flow cytometry. Results We demonstrated that stable CD155 expression was negatively correlated with prognosis in colorectal cancer patients. In vitro experiments confirmed that CD155 does not affect tumor cell proliferation, migration, or invasion. We also revealed that CD155 downregulated the function and migration of CD8+ T cells in vivo and in vitro. Furthermore, CD155 might regulate CD8+ T cells function via the PI3K/AKT/NF-κB pathway. Conclusion This study revealed that CD155 can promote the progression of colorectal cancer by regulating the PI3K / AKT-NF-κB pathway to promote the depletion of CD8+ T cells and reduce their migration to the tumor microenvironment. CD155 may become an important prognostic biomarker and an effective target for colorectal cancer immunotherapy.